Romanische Bibliographie (De Gruyter, 2005)
The Romanische Bibliographie has been published since 1923 as a supplement to Zeitschrift für romanische Philologie (est. 1877). It lists the bibliographical data for monographs, collected volumes, articles, and reviews published in the field of Romance Studies (both Literary Studies and Linguistics) with the exception of French Literary Studies. It is available both in print and online.